Critical functions of RhoB in support of glioblastoma tumorigenesis - Ma, Yufang (Neuro Oncol, 2015)
BACKGROUND: RhoB is a member of the Rho small GTPase family that regulates cytoskeletal dynamics and vesicle trafficking. The RhoB homologs, RhoA and RhoC, have been shown to promote cancer progression and metastasis. In contrast, the functions of RhoB in human cancers are context dependent. Although expression of RhoB inversely correlates with disease progression in several epithelial cancers, recent data suggest that RhoB may support malignant phenotypes in certain cancer types. METHODS: We assessed RhoB protein levels in glioma surgical specimens and patient-derived xenografts. The roles of RhoB in glioblastoma were determined by loss-of-function and gain-of-function assays in vitro and in vivo. The impact on p53 and STAT3 signaling was investigated. RESULTS: RhoB expression was similar in tumor specimens compared with normal neural tissues obtained from epilepsy surgery. RhoB was expressed in the vast majority of xenograft tumors and spheroid cultures. Knockdown of RhoB induced cell-cycle arrest and apoptosis and compromised in vivo tumorigenic potential. However, overexpression of wild-type RhoB or a constitutively active mutant (RhoB-V14) did not significantly affect cell growth, which suggests that RhoB is not a rate-limiting oncogenic factor and is consistent with the scarcity of RhoB mutations in human cancer. Knockdown of RhoB reduced basal STAT3 activity and impaired cytokine-induced STAT3 activation. In glioblastoma tumors retaining wild-type p53, depletion of RhoB also activated p53 and induced expression of p21(CIP1)(/WAF1). CONCLUSIONS: Our data suggest that RhoB belongs to an emerging class of “nononcogene addiction” factors that are essential for maintenance of malignant phenotypes in human cancers.